(untitled) (Comparative & International Education Series, 2021)
Global economic and political trends are increasingly impacting global student mobility patterns. This study sought to understand how changing economic, political, and social factors impact international students’ career and life choices. This comparative case study explored the experiences of 14 international students who studied in the U.S. and entered the global workforce between the years 2010 and 2017. Results include follow-up findings about the immediate career impacts of COVID-19. Although most of the participants were working in the U.S. at the time of the study, findings suggest that the uncertainty brought on by changing visa policies have negatively impacted the career paths of the study’s participants. However, prior to COVID-19, improving job markets in students’ home countries were resulting in increased willingness to return and work.